Prevalence, Evolution, and Risk Factors for Advanced Liver Fibrosis in Adults Undergoing Intestinal Transplantation. Issue 7 (13th March 2018) - Huard, Geneviève; Fiel, M. Isabel; Moon, Jang; Iyer, Kishore; Schiano, Thomas D.
Abstract: Introduction: Intestinal failure–associated liver disease (IFALD) occurs commonly in intestinal transplant (ITx) candidates receiving parenteral nutrition (PN). The aim of this study is to establish the prevalence and risk factors for advanced liver fibrosis in adults at the time of ITx. Methods: Retrospective chart review of all ITx was performed in adults between January 2000 and May 2014. Advanced liver fibrosis was defined as stage 3 or stage 4 fibrosis. Results: Fifty‐three patients met the inclusion criteria. The mean age was 50.6 ± 10.9 years, and the majority were female (60.4%) and Caucasian (67.9%). The mean body mass index was 21.7 ± 3.8 kg/m 2 and the median duration of PN was 402 (interquartile range: 529) days. Advanced liver fibrosis at the time of ITx was found in 13 patients (24.5%). The multivariate analysis revealed that female gender and white race were significant predictors of advanced liver fibrosis. A total bilirubin >3.0 mg/dL for > a month prior to ITx was associated with an odds ratio of 8.9 for advanced fibrosis at the time of ITx but did not reach statistical significance ( P = 0.055). Conclusion: Close to one‐quarter of the ITx recipients had advanced liver fibrosis. In the current era of improved PN management, our data suggests that previously reported risk factors for IFALD, such as extreme short gut syndrome and PN duration, may have a lesser impact on development of liver fibrosis. A prolonged duration of bilirubin elevation may be associated with advanced liver fibrosis in patients with IFALD, but this requires validation in a larger cohort.